Implementation of Parking Management Policy in Addressing Illegal Parking Attendants on Cipto Mangunkusumo Street, Cirebon City - Fery Febriyanshah; Mukarto Siswoyo (Asosiasi Dosen Muda Indonesia, 2026)
Illegal parking attendants remain a public service issue in urban transportation management, particularly on Cipto Mangunkusumo Street, Cirebon City, where high parking demand, limited official parking spaces, and weak public compliance contribute to traffic disorder and unauthorized parking practices. This study aims to analyze the implementation of parking management policy by the Cirebon City Transportation Agency in addressing illegal parking attendants, including the obstacles encountered and the efforts made to improve policy effectiveness. This research used a qualitative descriptive method, with data collected through interviews, field observations, and document analysis. The analysis was based on Van Meter and Van Horn’s policy implementation model, which includes policy standards and objectives, resources, characteristics of implementing agencies, inter-organizational communication, implementer disposition, and social-economic conditions. The results show that the policy has been implemented according to applicable regulations and standard operating procedures, but its implementation has not been fully optimal. The main obstacles include limited supporting facilities, insufficient surveillance infrastructure, inconsistent inter-agency coordination, low public awareness, and the economic dependence of some illegal parking attendants on parking activities. The discussion indicates that policy enforcement requires not only legal action but also persuasive, social, and economic approaches. This study concludes that strengthening coordination, improving infrastructure, and providing alternative livelihood strategies are necessary to enhance sustainable parking management in Cirebon City.